The Intelligent Auto-Tuning Controller Design Based on Dolphin Echo Location for Blood Glucose Monitoring System (Journal of Engineering, 2021)
This paper presents an enhancement technique for tracking and regulating the blood glucose level for diabetic patients using an intelligent auto-tuning Proportional-Integral-Derivative PID controller. The proposed controller aims to generate the best insulin control action responsible for regulating the blood glucose level precisely, accurately, and quickly. The tuning control algorithm used the Dolphin Echolocation Optimization (DEO) algorithm for obtaining the near-optimal PID controller parameters with a proposed time domain specification performance index. The MATLAB simulation results for three different patients showed that the effectiveness and the robustness of the proposed control algorithm in terms of fast generating insulin control action and tracking the dynamics behavior of the blood glucose level of the diabetic patients through minimizing overshoot, rise time and settling time in the transient state as well as the steady-state blood glucose level error is reduced approximately to zero and keep it in the desired glucose level, especially when we added a meal as disturbance effect.